Management and site conditions drive carbon dynamics of Forest understory vegetation - Delin, Emily (2021)
The forest understory vegetation is largely disregarded in studies of carbon sequestration despite notable contribution to storage and cycling in the ecosystem. In addition to already lacking knowledge on this pool independently, further uncertainty and change is introduced by forest management and the changing climate. Using data from the Swedish NFI and Generalized Linear Mixed Models, we modelled the dynamics of this terrestrial carbon pool under conditions created by management and site characteristics. In order to do so, understory vegetation was categorized into the species groups graminoids, forbs, dwarf shrubs, bryophytes, and lichens. This was done due to differences in carbon storage and turnover of the groups as well as available biometric functions. Total understory carbon decreased with increasing stand basal area, percent of spruce, and temperature and increased with stand age, CN ratio, and precipitation. Graminoids were negatively influenced by stand basal area, percent of spruce, stand age, and CN ratio and positively influenced by temperature. Bryophytes were positively influenced by stand basal area and percent of spruce and were negatively influenced by stand age and precipitation. Lichens were negatively influenced by stand age, percent of spruce, and precipitation and were positively influenced by CN ratio and temperature. Dwarf shrubs were positively influenced by stand age, CN ratio, temperature, and precipitation and were negatively impacted by higher percent of spruce. Forbs were negatively influenced by stand age, CN ratio, and temperature and were positively impacted by basal area. Based on climate projections towards higher average temperature and increased drought events, as well as popular management techniques, this indicates future higher turnover of carbon within this pool. These dynamics should be further studied alongside the overstory pool in order to ensure balance between all ecosystem services provided.